2023
DOI: 10.1111/aogs.14734
|View full text |Cite
|
Sign up to set email alerts
|

Identification of depression and anxiety during pregnancy: A systematic review and meta‐analysis of test accuracy

Elisabet Rondung,
Pamela Massoudi,
Katri Nieminen
et al.

Abstract: IntroductionDepression and anxiety are significant contributors to maternal perinatal morbidity and a range of negative child outcomes. This systematic review and meta‐analysis aimed to review and assess the diagnostic test accuracy of selected screening tools (Edinburgh Postnatal Depression Scale [EPDS], EPDS‐3A, Patient Health Questionnaire [PHQ‐9]‐, PHQ‐2, Matthey Generic Mood Question [MGMQ], Generalized Anxiety Disorder scale [GAD‐7], GAD‐2, and the Whooley questions) used to identify women with antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…The most commonly used standardized tool for this purpose is the Edinburgh Postnatal Depression Scale (EPDS), a self-report screening instrument used with various cutoff scores to detect signs of risk or a high probability of a major depressive disorder diagnosis. However, such results are more precisely applicable to the postnatal period, and a review on this topic ( 26 ) indicated that, in the assessment of pregnant women, the EPDS result should be associated with a clinical evaluation by a specialized professional. Building on this premise, the use of the PRIME-MD in evaluating depressive symptoms in pregnant women becomes a more favorable possibility as it contains within its structure the DSM-III diagnostic criteria for major depressive disorder, serving as a guide for specialized clinical interviews.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used standardized tool for this purpose is the Edinburgh Postnatal Depression Scale (EPDS), a self-report screening instrument used with various cutoff scores to detect signs of risk or a high probability of a major depressive disorder diagnosis. However, such results are more precisely applicable to the postnatal period, and a review on this topic ( 26 ) indicated that, in the assessment of pregnant women, the EPDS result should be associated with a clinical evaluation by a specialized professional. Building on this premise, the use of the PRIME-MD in evaluating depressive symptoms in pregnant women becomes a more favorable possibility as it contains within its structure the DSM-III diagnostic criteria for major depressive disorder, serving as a guide for specialized clinical interviews.…”
Section: Introductionmentioning
confidence: 99%